Identification and odor exposure regulation of odorant-binding proteins in Picromerus lewisi - Yi, Shan-Cheng; Yu, Jia-Ling; Abdelkhalek, Sara Taha; Sun, Zhi-Rong; Wang, Man-Qun (Frontiers in Physiology, 2024)
The highly developed sensitive olfactory system is essential for Picromerus lewisi Scott (Hemiptera: Pentatomidae) adults, an widely distributed natural predatory enemy, to locate host plants. During this process, odorant-binding proteins (OBPs) are thought to have significant involvement in the olfactory recognition. However, the roles of OBPs in the olfactory perception of P. lewisi are not frequently reported. Here, we conducted odor exposure and transcriptome sequencing experiments using healthy and Spodoptera litura-infested tobacco plants as odor sources. The transcriptomic data revealed that the alteration in the expression of mRNA levels upon exposure to odor was sex-dependent. As the expression profiles differed significantly between male and female adults of P. lewisi. A total of 15 P. lewisi OBPs (PlewOBPs) were identified from the P. lewisi transcriptome. Sequence and phylogenetic analysis indicated that PlewOBPs can be classified into two subfamilies (classic OBP and plus-C OBP). The qRT-PCR results showed that the transcript abundance of 8 PlewOBPs substantially altered following exposure to S. litura-infested tobacco plants, compared to the blank control or healthy plants. This implies that these PlewOBPs may have an olfactory function in detecting S. litura-infested tobacco plants. This study establishes the foundation for further understanding of the olfactory recognition mechanism of P. lewisi and helps discover novel targets for functional characterization in future research.